2020
DOI: 10.15446/acag.v69n2.60246
|View full text |Cite
|
Sign up to set email alerts
|

Water requirements and restrictions to sugarcane in cane plants and ratoon cane cycles in Southern Brazil

Abstract: In a site with a Cfa-type climate in southern Brazil, the water requirements and restrictions for the cultivation of sugar cane (Saccharum spp.), in plant and soca (second cut) were characterized. Water availability was calculated based on the daily water balance and evapotranspiration was estimated using the Penman-Monteith method. The thermal and water requirements of sugarcane were calculated taking as reference the agroecological zoning in the state of Paraná, Brazil. Water requirement index did not show l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In December before the sugarcane first ratoon has been harvested, crop water requirements were zero, because this month in this study was a dry-off period of the sugarcane first ratoon to improve sugarcane quality. [21] found that sugarcane needs supplemental irrigation of 508.8 mm/season to cane plant and 486.5 mm/season to ratoon cane with a higher frequency of irrigation in the development phase II.…”
Section: Crop Water Requirements (Cwr)mentioning
confidence: 99%
See 1 more Smart Citation
“…In December before the sugarcane first ratoon has been harvested, crop water requirements were zero, because this month in this study was a dry-off period of the sugarcane first ratoon to improve sugarcane quality. [21] found that sugarcane needs supplemental irrigation of 508.8 mm/season to cane plant and 486.5 mm/season to ratoon cane with a higher frequency of irrigation in the development phase II.…”
Section: Crop Water Requirements (Cwr)mentioning
confidence: 99%
“…The reduced competition of sugarcane for nutrients, moisture and light might have helped in profuse tiller production and low shoot mortality resulting in realizing a higher number of millable canes [32]. [21] reported that water stress restricted photosynthesis, elongation and lateral enlargement. [33] were observed that the furrow method, when irrigation was applied at longer intervals.…”
Section: Effect Of Deficit Irrigation On Cane Yield Parameters At Dif...mentioning
confidence: 99%
“…Sugarcane yields were modeled for three different phenological phases of ratoon sugarcane [20]. Phase I runs from July to October for a total of 93 days when sprouting and intense tillering occur.…”
Section: Adjustment Of the Multiple Linear Regression Modelmentioning
confidence: 99%